Alternativas metodológicas para el cálculo de las series retrospectivas regionales de EPA tras el cambio en la Clasificación Nacional de Actividades Económicas - José M. Pavía; Francisco Fabuel; Francisco G. Morillas (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2012)
– In order to overcome the potential loss of information that the transition to the new National Classification of Economic Activities could provoke in EPA series, INE has proposed a methodology to link CNAE 1993 and CNAE 2009 series. The procedure is based on employing a national transition matrix over division data. Regional labor markets, however, differ from the national one and additionally regional series are not generally available at the division level. This paper examines the impact that in the linked series should have (i) working at a level of aggregation above division and (ii) using a regional transition matrix. Focusing employment series published for the Valencian region, this research shows that (a), at the sectorial level, results do not depend on use of either the Spanish transition matrix of Spain or the Valencian one and also they are independent of the order in which aggregation of the divisions takes place and that (b), at the branch of activity, it is preferable to work with an own regional matrix.
Keywords: C18; C82; J00; 330; CNAE; active population survey; INE; time series